Integrating ‘Urf in the Legality of E-Commerce Transactions: Islamic Legal Analysis and Educational Management Implications of the COD Inspect First Method on Shopee - Muhammad Rohmat Hidayat; Nur ‘Azah; Masrokhin; Khoirul Anwar; Vian Hanes Andreastya; Ninik Azizah; Sirojuddin Abror (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2025)
The rapid development of digital technology has transformed conventional buying and selling practices, particularly through e-commerce platforms such as Shopee. Among its prominent features, the Cash on Delivery (COD) Inspect First method allows consumers to verify products before making payment. This study analyzes the legitimacy of the COD Inspect First method under Islamic law using the concept of ‘urf (customary practice) and explores its educational management implications for Islamic higher education institutions. Using a qualitative descriptive approach with a case study design, the study integrates normative juridical analysis, literature review, and observations of Shopee’s COD practices. Findings indicate that COD Inspect First constitutes a valid custom (‘urf shahih) as it is widely adopted, consistently applied, and does not contradict Qur’anic injunctions or hadith. The system promotes fairness, transparency, and mutual consent, aligning with the maqasid al-shariah (objectives of Islamic law). From an educational management perspective, the study highlights the urgency of integrating digital commerce literacy, Islamic economic ethics, and technology-based learning strategies into higher education curricula. These innovations are essential for preparing graduates to navigate the complexities of modern digital economies responsibly while upholding Islamic moral values.